ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MASYARAKAT SUKU AKIT TIDAK MELANJUTKAN PENDIDIKAN FORMAL DI DESA SOKOP KECAMATAN RANGSANG PESISIR KABUPATEN KEPULAUAN MERANTI - Khotimah, Husnul; ', Hambali; ', Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The Tribe Akit community is one of the remote communities in Riau, one of them is in Sokop Village, District of Rangsang Pesisir of Meranti Regency, where the Akit Tribe is included in Remote Indigenous Community (KAT). Based on the phenomenon that occurs Akit Tribe people who have dropped out of school for formal education from elementary school (SD), junior high school (SMP), High School (SMA), and Higher Education. Akit Tribe Society has the same rights as other tribes in getting education, this is in accordance with Article 31 Paragraph 1 of the 1945 Constitution which states that "every citizen is entitled to educationâ€. This research is purpose to find out what factors affecting in akit tribal communities uncontinued in formal education in sokop village sub district of coastal rangsang meranti archipelago district. The respondent in this research was 75 of akit tribes who uncontinued in formal education. Data collection techniques used; observation, questionnaires, interviews, documentation and literature. The research of this method used descriptive qualitative method. Based on the result of this research can be concluded the percentage recapitulation of the respondentsquestionnaire answers about the analysis of factors affecting akit tribal communities uncontinued informal education that is due the parents economic factor in which 73.22% giving "yes" statement and 26.78% giving "no" statement, This is seen from the sub indicators about the parents economic factor affecting tribal communities uncontinued formal in education.Keyword: Akit tribe, The factor, uncontinued education